2004
DOI: 10.1007/s00425-003-1192-3
|View full text |Cite
|
Sign up to set email alerts
|

NADH-dependent metabolism of nitric oxide in alfalfa root cultures expressing barley hemoglobin

Abstract: Transgenic alfalfa ( Medicago sativa L.) root cultures expressing sense and antisense barley ( Hordeum vulgare L.) hemoglobin were examined for their ability to metabolize NO. Extracts from lines overexpressing hemoglobin had approximately twice the NO conversion rate of either control or antisense lines under normoxic conditions. Only the control line showed a significant increase in the rate of NO degradation when placed under anaerobic conditions. The decline in NO was dependent on the presence of reduced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(68 citation statements)
references
References 25 publications
5
63
0
Order By: Relevance
“…These observations, corroborated by the direct correlation between weight of shoots and AHb1 level observed after exposure of wild-type and transgenic Arabidopsis plants to hypoxic stress (Figure 6) and by the large accumulation of NO observed in hypoxic root cultures of hemoglobin-deficient alfalfa (Dordas et al, 2003b) and maize (Zea mays) mutants (Dordas et al, 2004), support the hypothesis that stress-induced hemoglobins may function as NO dioxygenases (Dordas et al, 2003a;Igamberdiev et al, 2004) protecting against nitrosative stress associated with hypoxia and confirm that AHb1 metabolizes NO in vivo.…”
Section: Functional Effects Of Ahb1 In Transgenic Plantssupporting
confidence: 62%
See 1 more Smart Citation
“…These observations, corroborated by the direct correlation between weight of shoots and AHb1 level observed after exposure of wild-type and transgenic Arabidopsis plants to hypoxic stress (Figure 6) and by the large accumulation of NO observed in hypoxic root cultures of hemoglobin-deficient alfalfa (Dordas et al, 2003b) and maize (Zea mays) mutants (Dordas et al, 2004), support the hypothesis that stress-induced hemoglobins may function as NO dioxygenases (Dordas et al, 2003a;Igamberdiev et al, 2004) protecting against nitrosative stress associated with hypoxia and confirm that AHb1 metabolizes NO in vivo.…”
Section: Functional Effects Of Ahb1 In Transgenic Plantssupporting
confidence: 62%
“…In the presence of saturating concentrations of NO, the specific activity of AHb1 was 24 nmol/ min/mg. Because methemoglobin reductase activity was found in alfalfa (Medicago sativa) root cultures (Igamberdiev et al, 2004), it is possible that AHb1 activity may be augmented in vivo by specific interaction with a reductase system, as suggested for barley (Hordeum vulgare) hemoglobin (Igamberdiev et al, 2004) and demonstrated for human myoglobin (Flogel et al, 2001).…”
Section: Characteristics Of Recombinant Ahb1 and Reaction With Nomentioning
confidence: 99%
“…Among potential cellular targets for CN -or NO would be hemoproteins, such as cytochromes, hemoglobins, heme-containing reductases and heme-containing oxidases (e.g., Kundu et al 2003;Igamberdiev et al 2004). NO, in addition can S-nitrosylate plant proteins (Lindemayr et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The very high oxygen affinity, due to a very low dissociation rate constant, means that AHb1 strongly stabilizes O 2 after binding, thus ruling out a possible function related to O 2 sensing, carrying, or storing (6), whereas a role in electron transport is unlikely because of its high redox potential (7,8). As suggested in general for class 1 nsHbs (9), and proved in vivo for maize and alfalfa lines overexpressing class 1 nsHbs (8,10), AHb1 may participate in NO detoxification by acting as NO scavenger under hypoxic stress. In fact, the rapid nitrate accumulation from the reaction of oxyAHb1 with NO in vitro may be physiologically relevant in vivo to reduce the levels of NO under hypoxic stress (11,12).…”
Section: Introductionmentioning
confidence: 78%